TURNER SYNDROME – AN UNUSUAL CAUSE FOR AORTIC DISSECTION - Augusto, Rita (2021)
Turner syndrome (TS) is a disorder of female development with cardinal features of short stature and congenital cardiovascular defects. Congenital or acquired cardiological problems occur commonly in TS, being potentially progressive and responsible for severe complications, such as aortic dissection in young women. Accordingly, we describe a case of type A aortic dissection occurring in a woman with TS, highlighting the need to prioritize investigation in those patients to avoid a catastrophic aortic scenario.